Motivation, Punishment, dan Supervision, Pengaruhnya Terhadap Kinerja Karyawan Outsourcing (Studi Kasus Perusahan Syariah PT PRS Gresik) - Atho’illah, Akhmad Yunan; Andrian, Tito (LAN TABUR : Jurnal Ekonomi Syariah, 2025)
The workforce is the driving force of company activities. Therefore, companies need workers to carry out company operational activities. There are two work agreements regulated in Article 56 paragraph (2) of Law No. 13 of 2003 concerning employment, namely the Fixed Term Work Agreement (PKWT) and the Indefinite Term Work Agreement (PKWTT). Not a few companies use PKWT, such as PT Putera Rackindo Sejahtera. 64% of its employees are PKWT. This is because PKWT employees have better performance compared to PKWTT employees. The company provides pressure in the form of punishment and strict supervision to regulate the workforce so that they can work well. The results of the study showed that the performance of PKWT employees was 4% better than the performance of PKWTT employees Keywords: Motivation; Punishment; Supervision; Performance; Employee Outsourcing